China's great transformation : selected essays on Confucianism, modernization, and democracy - King, Ambrose Y. C. (The Chinese University Press, 2018)
Any consideration of China's cultural modernity must begin with a rethinking of traditional Chinese civilization in its orientation and the problems that it has to face in the modern age. This book examines how Confucian traditions have shaped modernity in East Asia. A leading sociologist, Ambrose Y.C. King discusses how China and East Asia developed a model of modern civilization distinct from the Western model of modernization which involves not only a process of deconstructing the cultural tradition but also a process of reconstructing it. He shows how the experience of modernization diverges within different Chinese societies, namely Hong Kong, Mainland China, and Taiwan. By highlighting the impact of Confucianism on the direction of modernity in Chinese societies, he argues that Confucianism contains the seeds of modernization and transformation and that in the right institutional settings these seeds could bear fruit to influence positively the course of development. The chapters of the book also explore Confucian networks and the development of capitalist economies, democratic governance, and moral education. The author focuses his analyses on how Confucian ideas and values underpinning the foundation of East Asian societies including social civility, political governance, the role of the family, individual self-cultivation, and moral regulation, matter to the modern social and political transformations of Chinese societies today.